Slug and E-Cadherin: Stealth Accomplices? - Sterneck, Esta; Poria, Dipak K.; Balamurugan, Kuppusamy (Frontiers in Molecular Biosciences, 2020)
During physiological epithelial-mesenchymal transition (EMT), which is important for embryogenesis and wound healing, epithelial cells activate a program to remodel their structure and achieve a mesenchymal fate. In cancer cells, EMT confers increased invasiveness and tumor-initiating capacity, which contribute to metastasis and resistance to therapeutics. However, cellular plasticity that navigates between epithelial and mesenchymal states and maintenance of a hybrid or partial E/M phenotype appears to be even more important for cancer progression. Besides other core EMT transcription factors, the well-characterized Snail-family proteins Snail (SNAI1) and Slug (SNAI2) play important roles in both physiological and pathological EMT. Often mentioned in unison, they do, however, differ in their functions in many scenarios. Indeed, Slug expression does not always correlate with complete EMT or loss of E-cadherin (CDH1). For example, Slug plays important roles in mammary epithelial cell progenitor cell lineage commitment and differentiation, DNA damage responses, hematopoietic stem cell self-renewal, and in pathologies such as pulmonary fibrosis and atherosclerosis. In this Perspective, we highlight Slug functions in mammary epithelial cells and breast cancer as a “non-EMT factor” in basal epithelial cells and stem cells with focus reports that demonstrate co-expression of Slug and E-cadherin. We speculate that Slug and E-cadherin may cooperate in normal mammary gland and breast cancer/stem cells and advocate for functional assessment of such Slug+/E-cadherinlow/+ (SNAI2+/CDH1low/+) “basal-like epithelial” cells. Thus, Slug may be regarded as less of an EMT factor than driver of the basal epithelial cell phenotype.